PROBLEMATIKA PELAKSANAAN RESTRUKTURISASI KREDIT MACET AKIBAT COVID-19 BERDASARKAN PERATURAN OTORITAS JASA KEUANGAN NOMOR 11/POJK.03/2020 (Studi BPR Sami Makmur) - Yuniar, Nirda Okta; Imanullah, Moch. Najib (Jurnal Privat Law, 2024)
This article this thesis law aims to review legal issues to see the implementation of bad credit restructuring due to Covid-19 by BPR Sami Makmur in accordance with the Financial Services Authority Regulation (POJK) Number 11 / POJK.03 / 2020 as well as prohibitions and alternative solutions that can be applied to problems in implementation. bad debt restructuring due to Covid-19 by BPR Sami Makmur in accordance with the Financial Services Authority Regulation (POJK) Number 11 / POJK.03 / 2020.The research method which is empirical legal research is descriptive analytical. The sources of legal materials used are primary and secondary legal materials. The research approach technique used a qualitative approach method. Data observation techniques used document study, interview or observation, observation or observation. The technique of analyzing legal materials uses a syllogistic method that uses a deductive mindset.These results indicate that the implementation of bad debt restructuring is carried out through changes in loan interest rates, additional credit ceilings, extension of credit terms, changes in interest arrears and loan principal, collateral auction or liquidation to simple lawsuit filing. The results of this study also show that during the implementation of the restructuring, including the debtor's lack of education / understanding regarding the restructuring, the debtor does not meet the debt restructuring debtor category, the debtor does not carry out the contents of the credit restructuring according to the agreement.